ANALYSIS OF THE USE OF COMBINE HARVESTER ON THE INCOME OF RICE FARMERS IN CINTA DAMAI VILLAGE, PERCUT SEI TUAN DISTRICT, DELI SERDANG REGENCY - Laurensius Parsaulian Sitinjak; Iskandarini; Rulianda P Wibowo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This increase in rice productivity must also be accompanied by an increase in the quality of the rice produced, namely rice that is able to meet demands and suit consumer preferences. The use of combine harvester harvesting machines can benefit farmers, because combine harvesters make it easier for farmers to harvest rice, shorten harvest time, reduce costs during harvest and can overcome the difficulty of finding workers during the main harvest. The aim of this research is: To analyze rice production before and after using Combine Harvester technology. To analyze rice farmers' income before and after using Combine Harvester technology. The data collected in this research used quantitative data analysis with descriptive statistical techniques. For quantitative data, use the average difference test (t-test). The results of this research were that the amount of rice production after using the combine was greater because the grain was clean, not mixed with dirt from empty grain and rubbish such as grass, rice stalks and rice leaves did not enter the sack, whereas before using the combine harvester the grain was still dirty and still a lot of empty grain droppings into the sack. Farmers' income before using combine harvester technology is lower than farmers who have used combine harvester technology, this is because using a combine harvester machine can cut production costs and reduce losses during harvesting activities and the amount of labor needed before using this tool. more than after using a combine harvester, so it will have an impact on increasing rice production and the income of farmer users.